(untitled) (Western European Journal of Medicine and Medical Science, 2025)
The study of personality as a central object of psychology is characterized by its complexity and versatility. The individual is the sum of the individual’s characteristics, experiences, values, social relationships and inner world, which are influenced by various factors in its formation and development. The main goal of personality psychology is to understand the psychological structure, internal processes, behavior and consciousness of the individual and to study their interaction with the social environment. This article provides information about the individual and his significant problems in psychology